Removal of Silver(I) from Aqueous Solutions with Low-Rank Turkish Coals - Abdülkerim Karabakan; Solmaz Karabulut; Adil Denizli; Yuda Yürüm (Adsorption Science & Technology)
The removal of silver ions from aqueous solutions containing low-to-moderate levels of contamination using Turkish Beypazari low-rank coal was investigated. Carboxylic acid and phenolic hydroxyl functional groups present on the coal surface provided adsorption sites for the removal of silver ions from solution via ion exchange. The equilibrium pH of the coal/solution mixture was shown to be the principal factor controlling the extent of recovery of Ag + ions from aqueous solutions. The optimum pH was measured as 4.0 and it was found that the maximum removal of silver from solution was achieved within 30 min. The maximum adsorption capacity of the Ag + ions was 1.87 mg/g coal. The adsorption phenomena appeared to follow a typical Langmuir isotherm. It was observed that the use of low-rank coal was considerably more effective in the recovery Ag + ions from aqueous solutions. Higher amounts of adsorbed Ag + ions could be desorbed (up to 92%) using 25 mM EDTA. Low-rank Turkish coals were suitable for consecutive use for more than 10 cycles without significant loss of adsorption capacity.